Implementasi Enterprise Resource Planning Berbasis SAP dalam Meningkatkan Kualitas Sistem Informasi Akuntansi Pada PT. BS Surabaya - Maria Christina Rahayu; Diana Zuhroh; Tjandra Wasesa; Wiratna Wiratna; Sutini Sutini (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
Enterprise Resource Planning (ERP) System - SAP is called "Industry Solu-tion" as a technological change that exists by changing the accounting in-formation system (AIS) process for company activities in running a busi-ness. In fact, the accounting and finance department has not adopted an SAP-based ERP system, while other departments in the company have im-plemented an SAP-based ERP system. This study aims to analyze the impact of SAP-based ERP implementation on efficiency, accuracy and data inte-gration in accounting information systems, by exploring differences be-tween departments that use and do not use the system. This type of research uses Descriptive qualitative methods by selecting PT BS Surabaya as a sample and source of informants from the Accounting and finance depart-ments who are considered to have knowledge and information about the problem under study, namely the implementation of SAP-based Enterprise Resource Planning (ERP) as an effort to improve the quality of accounting information systems at PT BS. Data collected using instruments in the form of observation and documentation, as well as in-depth interviews with in-formants. The data was analyzed qualitatively. The results showed that the implementation of SAP-based ERP significantly improved efficiency and accuracy in the departments that adopted it. And can make efficiency in the need for less labor compared to using manual methods.